2017
DOI: 10.3332/ecancer.2017.732
|View full text |Cite
|
Sign up to set email alerts
|

Highlights from the 15th St Gallen International Breast Cancer Conference 15–18 March, 2017, Vienna: tailored treatments for patients with early breast cancer

Abstract: The 15th St Gallen International Breast Cancer Conference was held in Vienna for the second time, from 15th–18th March 2017. 4000 people from 105 countries all over the world were invited to take part in the event. The real highlight of the conference was the last day with the International Consensus Session which was chaired by around 50 experts on breast cancer worldwide. With reference to data from scientific research, the consensus panel tried to offer guidelines for the management of breast cancer with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Studies have shown that the combined expression levels of ER, PR and HER2 into so‐called intrinsic molecular subtypes increases its prognostic and predictive value . The classification of tumours into luminal A, luminal B, HER2 positive and triple negative disease has been accepted by international panels that emphasise the importance to base therapeutic decisions on intrinsic molecular subtypes of breast cancer . Due to lacking data on gene expression levels, many studies use information on ER, PR and HER2 status which is based on immunohistochemistry to classify patients according to breast cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the combined expression levels of ER, PR and HER2 into so‐called intrinsic molecular subtypes increases its prognostic and predictive value . The classification of tumours into luminal A, luminal B, HER2 positive and triple negative disease has been accepted by international panels that emphasise the importance to base therapeutic decisions on intrinsic molecular subtypes of breast cancer . Due to lacking data on gene expression levels, many studies use information on ER, PR and HER2 status which is based on immunohistochemistry to classify patients according to breast cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a thoroughgoing estimation of a patient's prognosis is crucial to avoid overtreatment and that biological understanding helps us to escalate and de-escalate therapy even in high risk tumors 20 . In TNBC, few patients suffer recurrence between 5 and 10 years after surgery, and it is unlikely that chemotherapy exerts any major impact on late recurrence 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observation that FISH equivocal cases do not always reflect HER2 overexpression might suggest the growing need to carefully select patients who can benefit from HER2 targeted treatment. These concerns were widely debated during the 15th St Gallen International Breast Cancer Conference [ 46 ]. A randomised phase III trial, NSABP B47 is ongoing and will probably elucidate the best treatment approach for these patients.…”
Section: Discussionmentioning
confidence: 99%